Additive Manufacturing For Sustainable Custom-Designed Implants - Booysen, G.J.; van der Merwe, A.F.; de Beer, D.J. (South African Journal of Industrial Engineering, 2019)
Additive manufacturing (AM) has proven to be an attractive alternative manufacturing process compared with subtractive manufacturing (SM). Additive manufacturing has many advantages, such as mass customisation, less material wastage, and others listed in this article. However, the additive manufacturing of certified implants does not have the same degree of documentation and standardisation as the subtractive manufacturing process. As part of this research project, the problem statement is: “In offering additive manufacturing as an implant manufacturing solution, the complete process (design, manufacturing, and post-processing) had to be investigated in order to develop a certified manufacturing solution”.
Published Article